2021
DOI: 10.1536/ihj.20-627
|View full text |Cite
|
Sign up to set email alerts
|

Early Vascular Healing Following Bioresorbable-Polymer Sirolimus-Eluting Stent Placement Compared to That with Durable-Polymer Everolimus-Eluting Stent

Abstract: A recent thinner strut drug-eluting stent might facilitate early strut coverage after its placement. We aimed to investigate early vascular healing responses after the placement of an ultrathin-strut bioresorbable-polymer sirolimus-eluting stent (BP-SES) compared to those with a durable-polymer everolimus-eluting stent (DP-EES) using optical coherence tomography (OCT) imaging.This study included 40 patients with chronic coronary syndrome (CCS) who underwent OCT-guided percutaneous coronary intervention (PCI). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Oishi et al 21 reported the uncovered stent strut proportion of 29.6% at 2 weeks after O‐SES in patients with ST‐elevation myocardial infarction, indicating NIC and the elimination of atheromatous plaques in the early phase after O‐SES implantation. Furthermore, Ogura et al 22 reported the uncovered strut proportion of 2.9% at 1 month after O‐SES implantation in patients with SAP, thus describing favorable NIC. These processes of coronary arterial repair assessed by OCT are in conformity with the results from an in vitro study indicating that the passive coating of the stent surface with silicon carbide improved in‐stent endothelialization 23…”
Section: Discussionmentioning
confidence: 98%
“…Oishi et al 21 reported the uncovered stent strut proportion of 29.6% at 2 weeks after O‐SES in patients with ST‐elevation myocardial infarction, indicating NIC and the elimination of atheromatous plaques in the early phase after O‐SES implantation. Furthermore, Ogura et al 22 reported the uncovered strut proportion of 2.9% at 1 month after O‐SES implantation in patients with SAP, thus describing favorable NIC. These processes of coronary arterial repair assessed by OCT are in conformity with the results from an in vitro study indicating that the passive coating of the stent surface with silicon carbide improved in‐stent endothelialization 23…”
Section: Discussionmentioning
confidence: 98%